The healthy summer challenge: a community nutrition initiative - Best, Sarah (My University, 2025)
This integrated learning report provides a comprehensive review of my educational experience completing my Applied Practice Experience (APE). I completed this project with Utah State University (USU) Extension Create Better Health, the SNAP-Ed program for the state of Utah. Create Better Health’s goal is to help low-income families learn how to cook healthy meals on a budget, understand food nutrition facts labels, and promote other positive lifestyle changes. The program offers free online nutrition classes for adults and youth along with many other services. For this APE I designed and implemented a nutrition-based community health initiative, the “Healthy Summer Challenge,” for participants at the Summer Food Services Program for the Logan City School District in Logan, Utah. The goal of this project was to promote healthy eating behaviors in families, to recruit participants for Create Better Health’s SNAP-ed classes, and to increase nutrition knowledge of those who joined the challenge. Additionally, I created promotional materials, designed pre- and post- surveys, and put together an educational table display each week. The table display included physically active games for youth, nutrition education posters, a MyPlate display, healthy recipes, and samples from the recipe of the week. Parents or guardians were invited to fill out surveys, make healthy recipes at home with their families, and to attend Create Better Health SNAP-Ed classes. I offered two in-person class series: Create Better Health for adults, and Food, Fun, and Reading for youth. Online classes for Create Better Health for adults were also offered. To incentivize participation, participants were given raffle tickets for completing tasks in the challenge. Raffle winners were provided with gift cards which were donated by a local grocery store. After the challenge was completed, I used systems thinking tools to analyze ways to improve this project for future programming. I also presented the results to the Create Better Health leadership team to share insights into areas to improve for future implementation. This experience helped build my skills in program design, resource management, promotional material creation, data collection, communication, and utilization of systems thinking tools.
Keywords: Public health; Nutrition; Summer food service program; Promotional material creation; Data collection; Communication; Utilization of systems thinking tools